Analysis of the Thermal Behavior of Materials for Orthopedic Heels. Issue 1 (16th April 2021) - Cotoros, Diana; Druga, Corneliu; Repanovici, Angela; Stanciu, Anca
Abstract: The present paper proposes an experiment meant to determine the change of dimensions that may occur due to the increase of temperature of the orthopedic heels. The 3D model is manufactured using ethylene‐vinyl acetyl, also known as EVA, a copolymer made of ethylene and vinyl acetyl, which is very flexible and light weighted, also impermeable and UV and shock resistant. Five of the most used materials are analyzed during the experiment Orange Support, Blue Comfort, Multicolor, Green Relax, and Yellow Soft. Dimensions measurements are also taken five times a day for 5 days and recorded in tables and diagrams using Excel tools. In order to perform a statistical analysis of the results, the F‐Anova test is used and applied upon the recorded values. The conclusion is that there is a significant change of dimensions in the orthopedic heels materials that might affect the comfort of the users in certain conditions.